A high thermal conductivity and high corrosion resistance magnesium alloy suitable for mobile phone mid-plate and its preparation method and application

By adding Al, Ce, Nd, Sn and other elements to the magnesium alloy and using medium frequency induction smelting and die-casting processes, a high thermal conductivity and high corrosion resistance magnesium alloy is prepared, which solves the problem that traditional technology cannot meet the complex structure and functional needs of mobile phones, and achieves the lightweight, thermal conductivity and corrosion resistance of the material.

CN119243000BActive Publication Date: 2025-04-18SHANGHAI JIAOTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411782800.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-18
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing technology is difficult to meet the complex structure and functional needs of mobile phone mid-boards. Traditional aluminum alloy molding technology cannot achieve the manufacturing of complex geometric shapes. At the same time, magnesium alloys have shortcomings in thermal conductivity and corrosion resistance.

Method used

A high thermal conductivity and high corrosion resistance magnesium alloy is used, combined with elements such as Al, Ce, Nd, Sn and other elements with magnesium, and prepared by medium-frequency induction smelting and die-casting processes to form a material with high yield strength, tensile strength and good thermal conductivity. It is controlled by reasonable element ratio and process parameters to form a dense composite oxide film layer to improve corrosion resistance.

Benefits of technology

It has achieved lightweight, thermal conductivity and corrosion resistance of the board materials in mobile phones, can meet complex structure and functional needs, and improve production efficiency and overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243000B_ABST
    Figure CN119243000B_ABST
Patent Text Reader

Abstract

The present invention provides a high thermal conductivity and high corrosion resistance magnesium alloy suitable for a mobile phone mid-plate and a preparation method thereof, belonging to the technical field of magnesium alloy materials. The magnesium alloy is composed of the following elements in mass percentage: Al: 3.0-5.0%, Ce: 1.0-3.0%, Nd: 0.5-2.0%, Sn: 0.1-1.0%, impurity elements Fe≤0.06%, Cu≤0.004%, Ni≤0.002%, and the balance is magnesium. After 7 days of neutral salt spray test, the magnesium alloy of the present invention has a weight loss corrosion rate of 0.236 mm / y, a yield strength of 150-160 MPa, a tensile strength of 250-280 MPa, an elongation of 8-12%, and a thermal conductivity of 110-120 W / (m·K).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of magnesium alloy materials, and in particular relates to a high thermal conductivity and high corrosion resistance magnesium alloy suitable for a mobile phone mid-plate and a preparation method thereof. Background Art

[0002] The mid-board of a mobile phone is usually made of metal materials and is responsible for supporting a variety of electronic components such as the motherboard, processor, memory, and sensors. The thickness of the mid-board of a mobile phone is usually thin, about 0.5mm. In order to ensure that the mid-board can provide sufficient support, its material must have good mechanical properties. At the same time, in order to meet consumers' demand for lightweight, more and more mobile phone designs tend to use lightweight materials to reduce the weight and thickness of the overall device. In addition, if the heat generated by electronic components such as processors during operation is not dissipated in time, the temperature of the mid-board and its components will be too high, affecting their performance and stability.

[0003] Traditional mobile phone mid-plates are made of aluminum alloy strips. Chinese patent application CN201710710166.6 discloses a high-strength aluminum alloy strip for mobile phone mid-plates and a method for manufacturing the same. The invention uses an aluminum alloy strip for mobile phone mid-plates made by stamping, with a yield strength of 280-330MPa, a tensile strength of 370-400MPa, an elongation of ≥10%, and high thermal conductivity. However, this forming method is only applicable to relatively simple planar structures and mainly meets the supporting function of the mobile phone mid-plate. However, it is impossible to meet the manufacturing requirements of complex geometric shapes such as complex mobile phone internal component support structures and assembly positioning holes. Therefore, in the design and production process, it is urgent to explore more advanced forming technologies to meet the diverse requirements of mobile phone mid-plates in complex structures and functions.

[0004] Magnesium is the lightest engineering metal material with a density of 1.75 g / cm 3) is only 1 / 4 of steel and 2 / 3 of Al. The application of magnesium alloy in the middle plate of mobile phones can effectively reduce the weight of the body, thereby improving the convenience of carrying and user experience. Magnesium is also the most abundant light metal material on the earth, and has great application potential in lightweight products. However, magnesium alloys also have some defects when used as mobile phone middle plate materials, especially in terms of thermal conductivity and corrosion resistance. In terms of thermal conductivity, although the thermal conductivity of magnesium itself is relatively good, the thermal conductivity of magnesium alloys is poorer than that of copper or aluminum. This means that in application scenarios where high heat is handled (such as heat dissipation of high-performance processors), magnesium alloys may not be as effective as other metals. In addition, there may be problems with uneven microstructure inside the magnesium alloy, which will affect the overall heat conduction efficiency. In terms of corrosion resistance, on the one hand, magnesium is the most chemically reactive engineering metal, and its standard electrode potential is only 2.37V vs. SCE, which makes magnesium alloys, as sacrificial anodes, prone to severe corrosion when in contact with other structural metals; on the other hand, unlike aluminum alloys or stainless steel, which form dense corrosion passivation films with good protective properties during the corrosion process, the spontaneously formed oxide film of magnesium alloys is loose and porous, lacking in protective properties. Especially in environments with high salt content, magnesium alloys are more susceptible to corrosion.

[0005] With the continuous update and iteration of high-end smartphones, the requirements for mobile phone mid-plates are increasing, and the internal structure of mobile phones is becoming more and more complex. Traditional stamping aluminum alloy strips can no longer meet its design requirements. At the same time, the density of magnesium alloy is much lower than that of aluminum alloy, which helps to significantly reduce the weight of the body and improve the overall user experience. Therefore, it is urgent to develop a die-cast magnesium alloy with high strength, high thermal conductivity and high corrosion resistance suitable for mobile phone mid-plates to meet the rapid production and manufacturing needs of modern smartphone mid-plates. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of the prior art and provide a high thermal conductivity and high corrosion resistance magnesium alloy that can cope with the complex structure inside a mobile phone and is suitable for the middle plate of a mobile phone and a preparation method thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A first aspect of the present invention provides a high thermal conductivity and high corrosion resistance magnesium alloy, which is composed of the following elements in percentage by mass: Al: 3.0-5.0%, Ce: 1.0-3.0%, Nd: 0.5-2.0%, Sn: 0.1-1.0%, impurity elements Fe≤0.06%, Cu≤0.004%, Ni≤0.002%, and the balance is magnesium.

[0009] The present invention selects magnesium (Mg) as the main material. Magnesium is the lightest known engineering metal material with extremely high specific strength and specific stiffness, which makes the prepared alloy material have a significant lightweight effect. In the alloy design, Al, Ce, Nd, and Sn metal elements are selected to effectively improve the mechanical properties, corrosion resistance, and thermal conductivity of the magnesium alloy material. In terms of mechanical properties, by adding Al, Ce, Nd, and Sn, which have little effect on the thermal conductivity of magnesium, to pure magnesium, the strengthening phases Mg2Sn and Al2Sn are introduced. 11 Ce3 and Al2Nd effectively improve the yield strength and tensile strength of magnesium alloys. In terms of corrosion resistance, Al, Ce, and Nd oxides participate in the formation of corrosion film during the corrosion process, generating a uniform and dense composite oxide film that can effectively block the penetration of corrosive media, thereby protecting the internal magnesium matrix from further corrosion. In terms of thermal conductivity, due to the limited solid solubility of Ce, Nd, and Sn in magnesium, they are easily transformed from solid solution to precipitation in the magnesium matrix, forming Mg2Sn, Al 11 Ce3, Al2Nd second phase, a small amount of Ce, Nd and Sn addition reduces the degree of lattice distortion in the magnesium matrix, thereby effectively improving the thermal conductivity of the magnesium matrix.

[0010] In addition, the present invention needs to accurately control the proportion of alloy elements to achieve the best alloy performance. When the content of Al, Ce, Nd or Sn elements is too much or too little, it will cause grain coarsening or form an undesirable second phase, thereby reducing the overall mechanical properties of the material. When the content of Al, Ce, Nd or Sn elements is too much, the excessive precipitation of the second phase will aggravate the galvanic corrosion effect between the matrix and the corrosion, and too little element content will be unfavorable for the formation of a composite oxide film layer, reducing corrosion resistance. The addition of too many solute atoms will also cause Mg lattice distortion, enhance its scattering effect on electrons and phonons, hinder the free movement of electrons and phonons in the Mg lattice, reduce the mean free path of electrons and phonons, and thus reduce the thermal conductivity of the magnesium alloy.

[0011] The second aspect of the present invention provides a method for preparing the high thermal conductivity and high corrosion resistance magnesium alloy, comprising the following steps:

[0012] (1) Calculate and weigh the ingredients according to the composition ratio of the high thermal conductivity and high corrosion resistance magnesium alloy;

[0013] (2) Put pure magnesium ingots, tin particles and aluminum blocks into a medium frequency induction melting furnace, heat and melt them under a protective atmosphere, and keep them warm for a certain period of time;

[0014] (3) In a protective atmosphere, the temperature is raised, Mg-Ce and Mg-Nd master alloys are added, and after they are completely melted into a melt, they are stirred and kept warm for a certain period of time;

[0015] (4) Refining, degassing, slag removal, stirring under a protective atmosphere, standing and keeping warm for a certain period of time, pouring into a preheated mold and air cooling into an ingot to obtain a magnesium alloy casting;

[0016] (5) The obtained magnesium alloy casting is heated to be completely melted again and kept warm, while a nitrogen protective atmosphere is introduced, and then injected into a die-casting mold, and finally molded to obtain the high thermal conductivity and high corrosion resistance magnesium alloy.

[0017] In a preferred embodiment, the protective gas in step (2) is a mixed gas of SF6 and CO2, the heating temperature is 670-710°C, and the insulation time is 10-30 minutes.

[0018] In a preferred embodiment, the temperature in step (3) is raised to 720-760° C., and the insulation time is 5-20 min.

[0019] In a preferred embodiment, the specific weight percentage compositions of the Mg-Ce and Mg-Nd master alloys in step (3) are: Mg-30Ce and Mg-30Nd.

[0020] In a preferred embodiment, the insulation time in step (4) is 10 to 30 minutes.

[0021] In a preferred embodiment, the temperature in step (5) is raised to 680-750°C.

[0022] In a preferred embodiment, the die-casting mold in step (5) is pre-temperatured at 200-250° C. During the injection process, an injection speed of 2-5 m / s, an injection pressure of 70-90 MPa, a holding time of 5-20 s are adopted, and rapid cooling and molding are performed.

[0023] In the preparation method of the present invention, it is necessary to accurately control the temperature and time. Too high a temperature can easily lead to excessive grain growth, which will reduce the strength and toughness of the alloy, while small and uniform grains can usually provide better mechanical properties. Too low a temperature may cause uneven distribution of elements of different densities, resulting in component segregation, which in turn affects the uniformity and performance of the alloy. When the heating time is too long, long-term high temperature will cause more magnesium and its alloy elements to react with oxygen in the air, causing burns, and will also lead to uneven distribution of alloy components and decreased mechanical properties. Insufficient smelting time will result in the inability to completely dissolve the alloy elements, resulting in uneven alloy composition, and will also cause non-metallic inclusions to fail to fully float up and be removed, thereby affecting the purity and mechanical properties of the alloy.

[0024] The present invention adopts die casting process to form Mg near the grain boundary. 17 Al 12The dense network structure of the phase acts as a corrosion barrier for the magnesium matrix, effectively hindering the expansion of corrosion. In addition, for magnesium alloys, the oxide film layer with a PB ratio (Pilling-Bedworth ratio, the ratio of the volume of each metal ion in the oxide film generated by the combination of metal and oxygen on the metal surface to the volume of each metal atom in the metal) of 1-2 is relatively dense. The oxide film layer becomes loose when it is lower than 1, and the oxide film layer is too large to squeeze each other and produce cracks when it is higher than 2. The PB ratio of magnesium oxide is 0.81, the PB ratio of aluminum oxide is 1.26, and the rare earth oxide is between 1 and 2. The Al, Ce, and Nd oxides with high PB ratios participate in the formation of the corrosion film layer during the corrosion process, forming a uniform and dense composite oxide film layer, which can effectively block the penetration of the corrosive medium, thereby protecting the internal magnesium matrix from further corrosion.

[0025] The third aspect of the present invention provides the use of the high thermal conductivity and high corrosion resistance magnesium alloy in the preparation of a mobile phone mid-plate and a mobile phone mid-plate prepared from the high thermal conductivity and high corrosion resistance magnesium alloy.

[0026] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0027] 1. By adding Al, Ce, Nd, and Sn, which have little effect on the thermal conductivity of magnesium, into pure magnesium, the strengthening phases Mg2Sn, Al 11 Ce3 and Al2Nd effectively improve the yield strength and tensile strength of magnesium alloys.

[0028] 2. Through the die casting process, Mg is formed near the grain boundary 17 Al 12 The dense network structure of the phase acts as a corrosion barrier for the magnesium matrix, effectively hindering the expansion of corrosion; in addition, the Al, Ce, and Nd oxides with a high PB ratio participate in the formation of the corrosion film during the corrosion process, generating a uniform and dense composite oxide film, which can effectively block the penetration of the corrosive medium, thereby protecting the internal magnesium matrix from further corrosion; the synergistic effect of the two significantly improves the corrosion resistance of the die-cast alloy.

[0029] 3. Since the solid solubility of Ce, Nd and Sn in magnesium is limited, they are easily transformed from solid solution state to precipitation state in the magnesium matrix to form Mg2Sn, Al 11 Ce3, Al2Nd second phase, a small amount of Ce, Nd and Sn addition reduces the degree of lattice distortion in the magnesium matrix, thereby effectively improving the thermal conductivity of the magnesium matrix.

[0030] 4. The combination of die-casting and molding and its optimized parameters can effectively prevent defects such as fracturing, shrinkage and porosity in magnesium alloys during the casting process, and can meet the molding requirements of complex internal structures of mobile phones, and realize the molding of ultra-thin high-strength mobile phone structural components. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope photograph of the high thermal conductivity and high corrosion resistance magnesium alloy of Example 3 of the present invention.

[0032] Figure 2 This is a scanning electron microscope photograph of the high thermal conductivity and high corrosion resistance magnesium alloy of Example 3 of the present invention after being subjected to a salt spray corrosion test.

[0033] Figure 3 This is a scanning electron microscope photograph of the cross section of the high thermal conductivity and high corrosion resistance magnesium alloy of Example 3 of the present invention after salt spray corrosion test. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Embodiment 1-5:

[0036] A high thermal conductivity and high corrosion resistance magnesium alloy, the specific composition of which is shown in Table 1, the unit is wt.%, and the balance is Mg and inevitable impurities.

[0037] Table 1 Content of each element in the magnesium alloy of Examples 1-5

[0038]

[0039] The preparation method of the above-mentioned high thermal conductivity and high corrosion resistance magnesium alloy is as follows:

[0040] (1) Calculate and weigh the ingredients according to the composition ratio of the high thermal conductivity and high corrosion resistance magnesium alloy;

[0041] (2) Putting pure magnesium ingot, tin particles and aluminum blocks into a medium frequency induction melting furnace, heating to 680°C under a protective atmosphere, and keeping the temperature for 10 minutes after they are completely melted; the protective gas is a mixture of SF6 and CO2;

[0042] (3) In a protective atmosphere, the temperature is raised to 720° C., Mg, Mg-Ce, and Mg-Nd master alloys are added, and after they are completely melted into a melt, the mixture is stirred and kept warm for 10 minutes; the weight percentage of Ce and Nd in the Mg-Ce and Mg-Nd master alloys is 30%;

[0043] (4) Refining, degassing, slag removal, stirring under a protective atmosphere, standing still again and keeping warm for 20 minutes, pouring into a preheated mold and air cooling into an ingot to obtain a magnesium alloy casting;

[0044] (5) The obtained magnesium alloy casting is completely melted again at 720°C and kept warm while introducing a nitrogen protective atmosphere, and then injected into a die-casting mold, and finally a magnesium alloy with an average wall thickness of 0.5 mm is obtained by die-casting;

[0045] The temperature of the die-casting mold is maintained at 200-250° C. in advance; during the injection process, the injection speed is 3 m / s, the injection pressure is 80 MPa, the pressure holding time is 10 s, and rapid cooling and molding are performed.

[0046] Taking Example 3 as an example, the scanning electron microscope photo of the high thermal conductivity and high corrosion resistance magnesium alloy prepared in Example 3 is shown in the attached figure. Figure 1 shown.

[0047] Comparative Examples 1-4

[0048] This comparative example provides a magnesium alloy, the specific composition of which is shown in Table 2, in wt.%, and the remainder is Mg and unavoidable impurities.

[0049] Table 2 Content of each element in the magnesium alloy of Comparative Examples 1-4

[0050]

[0051] The preparation method of the magnesium alloy in the above comparative example is as follows:

[0052] (1) Calculate and weigh the ingredients according to the composition ratio of the magnesium alloy;

[0053] (2) Putting pure magnesium ingot, tin particles and aluminum blocks into a medium frequency induction melting furnace, heating to 680°C under a protective atmosphere, and keeping the temperature for 10 minutes after they are completely melted; the protective gas is a mixture of SF6 and CO2;

[0054] (3) In a protective atmosphere, the temperature is raised to 720° C., Mg, Mg-Ce, and Mg-Nd master alloys are added, and after they are completely melted into a melt, they are stirred and kept warm for 10 minutes; the weight percentage of Ce and Nd in the Mg-Ce and Mg-Nd master alloys is 30%;

[0055] (4) Refining, degassing, slag removal, stirring under a protective atmosphere, standing still again and keeping warm for 20 minutes, pouring into a preheated mold and air cooling into an ingot to obtain a magnesium alloy casting;

[0056] (5) The obtained magnesium alloy casting is completely melted again at 720°C and kept warm while introducing a nitrogen protective atmosphere, and then injected into a die-casting mold, and finally a magnesium alloy with an average wall thickness of 0.5 mm is obtained by die-casting;

[0057] The temperature of the die-casting mold is maintained at 200-250° C. in advance; during the injection process, the injection speed is 3 m / s, the injection pressure is 80 MPa, the pressure holding time is 10 s, and rapid cooling and molding are performed.

[0058] Comparative Example 5

[0059] This comparative example provides a magnesium alloy composed of the following elements in percentage by mass: Al: 4.31%, Ce: 1.94%, Nd: 1.37%, Sn: 0.44%, and the remainder being Mg and unavoidable impurities, wherein the impurity elements Fe=0.057%, Cu=0.0021%, and Ni=0.0012%.

[0060] The preparation method of the magnesium alloy is as follows:

[0061] (1) Calculate and weigh the ingredients according to the composition ratio of the high thermal conductivity and high corrosion resistance magnesium alloy;

[0062] (2) Putting pure magnesium ingot, tin particles and aluminum blocks into a medium frequency induction melting furnace, heating to 680°C under a protective atmosphere, and keeping the temperature for 10 minutes after they are completely melted; the protective gas is a mixture of SF6 and CO2;

[0063] (3) In a protective atmosphere, the temperature is raised to 720° C., Mg-Ce and Mg-Nd master alloys are added, and after they are completely melted into a melt, they are stirred and kept warm for 10 minutes; the weight percentage of Ce and Nd in the Mg-Ce and Mg-Nd master alloys is 30%;

[0064] (4) Refining, degassing, and stirring are performed under a protective atmosphere. After standing still again, the mixture is kept warm for 20 minutes and then poured into a preheated mold and air-cooled into an ingot to obtain a magnesium alloy casting.

[0065] Comparative Example 6

[0066] This comparative example provides a magnesium alloy composed of the following elements in percentage by mass: Al: 4.31%, Ce: 1.94%, Nd: 1.37%, Sn: 0.44%, and the remainder being Mg and unavoidable impurities, wherein the impurity elements Fe=0.057%, Cu=0.0021%, and Ni=0.0012%.

[0067] The preparation method of the magnesium alloy is as follows:

[0068] (1) Calculate and weigh the ingredients according to the composition ratio of the high thermal conductivity and high corrosion resistance magnesium alloy;

[0069] (2) Putting pure magnesium ingot, tin particles and aluminum blocks into a medium frequency induction melting furnace, heating to 680°C under a protective atmosphere, and keeping the temperature for 10 minutes after they are completely melted; the protective gas is a mixture of SF6 and CO2;

[0070] (3) In a protective atmosphere, the temperature is raised to 820° C., Mg-Ce and Mg-Nd master alloys are added, and after they are completely melted into a melt, the mixture is stirred and kept warm for 10 minutes; the weight percentage of Ce and Nd in the Mg-Ce and Mg-Nd master alloys is 30%;

[0071] (4) Refining, degassing, slag removal, stirring under a protective atmosphere, standing still again and keeping warm for 20 minutes, pouring into a preheated mold and air cooling into an ingot to obtain a magnesium alloy casting;

[0072] (5) The obtained magnesium alloy casting is completely melted again at 800°C and kept warm while introducing a nitrogen protective atmosphere, and then injected into a die-casting mold, and finally a magnesium alloy with an average wall thickness of 0.5 mm is obtained by die-casting;

[0073] The temperature of the die-casting mold is maintained at 200-250° C. in advance; during the injection process, the injection speed is 3 m / s, the injection pressure is 80 MPa, the pressure holding time is 10 s, and rapid cooling and molding are performed.

[0074] Performance test 1: Salt spray immersion test

[0075] The magnesium alloys prepared in Examples 1-5 and Comparative Examples 1-6 were subjected to a 7-day salt spray immersion test according to standard ISO 9227-2017, and the corrosion rate results were as follows:

[0076] Table 3 Salt spray immersion test results

[0077]

[0078] The above test results show that the corrosion rate of the high thermal conductivity and high corrosion resistance magnesium alloy prepared by the present invention in the salt spray immersion test does not exceed 0.30mm / y, which is lower than the corrosion rate of the ultra-pure magnesium alloy, and has excellent corrosion resistance. However, the element content in Comparative Examples 1-4 is too high, and the excessive precipitation of the second phase will aggravate the galvanic corrosion effect between the matrix and the substrate, accelerate the corrosion, and the corrosion rate exceeds 0.45mm / y. Comparative Example 5 is not subjected to the die-casting process. 17 Al 12 The phases are coarse and disorderly distributed, and cannot serve as an effective corrosion barrier to effectively hinder the expansion of corrosion; while in the pre-die-casting step of Comparative Example 6, the melting temperature of the magnesium alloy is too high, causing serious macro-segregation, coarsening the alloy grains, and reducing the corrosion resistance.

[0079] Taking Example 3 as an example, the scanning electron microscope photo of the high thermal conductivity and high corrosion resistance magnesium alloy prepared in Example 3 after the salt spray corrosion test is shown in the attached figure. Figure 2 The scanning electron microscope photo of the cross section after the salt spray corrosion test is shown in the attached Figure 3 shown.

[0080] Performance Test 2: Thermal Conductivity Test

[0081] The thermal conductivity of the magnesium alloys prepared in Examples 1-5 and Comparative Examples 1-6 was tested, and the results were as follows:

[0082] Table 4 Thermal conductivity test results

[0083]

[0084] The above test results show that the die-cast magnesium alloy material of the present invention has good thermal conductivity, and the thermal conductivity is 110-120W / (m·K). However, the element content of Comparative Examples 1-4 is too high, and the addition of solute atoms will cause Mg lattice distortion, thereby enhancing its scattering effect on electrons and phonons, hindering the free movement of electrons and phonons in the Mg lattice, and reducing the mean free path of electrons and phonons, thereby reducing the thermal conductivity of the magnesium alloy. Comparative Example 5 will have certain pores and uneven microstructures, and its thermal conductivity will be reduced to a certain extent compared with the embodiment. The grains of the magnesium alloy in Comparative Example 6 are coarse, and under excessively high temperature melting conditions, the magnesium alloy is easily oxidized to form impurities such as magnesium oxide, thereby reducing its thermal conductivity.

[0085] Performance test 3: Mechanical properties test

[0086] The magnesium alloys prepared in Examples 1-5 and Comparative Examples 1-6 were tested for yield strength, tensile strength and elongation in accordance with GB / T 228.1-2021, and the results are as follows:

[0087] Table 5 Mechanical properties test results

[0088]

[0089] The above test results show that the die-cast magnesium alloy material prepared by the present invention has good mechanical properties, a yield strength of 150-160MPa, a tensile strength of 250MPa-280MPa, and an elongation of 8-12%. However, in Comparative Examples 1-4, the alloy element content is too much, the solid solution strengthening effect is enhanced, and while the strength is improved, the elongation decreases, the brittleness increases, and it is easy to break or damage when subjected to impact or pressure. This will affect the durability of the material, especially when it falls or collides. In Comparative Example 5, the cooling rate of the magnesium alloy material after smelting is slow, and defects such as pores are easily formed, resulting in a lower strength of the magnesium alloy material and a lower elongation. In Comparative Example 6, the smelting temperature is too high, which will result in coarse alloy grains. The coarse grain structure will reduce the strength and elongation of the material.

[0090] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high thermal conductivity and high corrosion resistance magnesium alloy, composed of the following elements in percentage by mass: composition: Al: 3.0-5.0%, Ce: 1.0-3.0%, Nd: 0.5-2.0%, Sn: 0.1-1.0%, impurity elements Fe≤0.06%, Cu≤0.004%, Ni≤0.002%, the balance is magnesium; The method for preparing the high thermal conductivity and high corrosion resistance magnesium alloy comprises the following steps: (1) Calculate and weigh the ingredients according to the composition ratio of the high thermal conductivity and high corrosion resistance magnesium alloy; (2) Put pure magnesium ingots, tin particles and aluminum blocks into a medium frequency induction melting furnace, heat and melt them under a protective atmosphere, and keep them warm; (3) In a protective atmosphere, heat up, add Mg-Ce and Mg-Nd master alloys, and stir and keep warm after they are completely melted into a melt; (4) Refining, degassing, slag removal, stirring under a protective atmosphere, standing still again and keeping warm, pouring into a preheated mold and air cooling into an ingot to obtain a magnesium alloy casting; (5) The obtained magnesium alloy casting is heated to 680-750° C. and completely melted again and kept warm, while introducing a nitrogen protective atmosphere, and then injected into a die-casting mold, and finally molded to obtain the high thermal conductivity and high corrosion resistance magnesium alloy; The die-casting mold is kept at a temperature of 200-250° C. in advance; during the injection process, an injection speed of 2-5 m / s, an injection pressure of 70-90 MPa, a holding time of 5-20 s are adopted, and rapid cooling and molding are performed; The corrosion rate of the high thermal conductivity and high corrosion resistance magnesium alloy in a salt spray immersion test does not exceed 0.30 mm / y, and the thermal conductivity is 110-120 W / (m·K).

2. The high thermal conductivity and high corrosion resistance magnesium alloy according to claim 1, characterized in that: The protective gas described in step (2) to step (4) is a mixed gas of SF6 and CO2.

3. The high thermal conductivity and high corrosion resistance magnesium alloy according to claim 2, characterized in that: The heating temperature in step (2) is 670-710° C., and the insulation time is 10-30 min.

4. The high thermal conductivity and high corrosion resistance magnesium alloy according to claim 3, characterized in that: Step (3) The temperature is raised to 720-760° C., and the insulation time is 5-20 minutes.

5. The high thermal conductivity and high corrosion resistance magnesium alloy according to claim 4, characterized in that: The weight percentage of Ce in the Mg-Ce master alloy described in step (3) is 30%, and the weight percentage of Nd in the Mg-Nd master alloy is 30%.

6. The preparation method according to claim 1, characterized in that: The insulation time in step (4) is 10 to 30 minutes.

7. Use of the high thermal conductivity and high corrosion resistance magnesium alloy according to claim 1 in the preparation of mobile phone mid-plates.

Citation Information

Patent Citations

  • High-strength mobile phone medium plate aluminum alloy strip and preparing method thereof

    CN107475583A

  • Mg alloy anode material and preparation method thereof

    CN105925862A

  • Extrusion casting magnesium alloy material and preparation method thereof

    CN108977710A